Penafsiran Surah Al-Baqarah Ayat 148 (Studi Kasus MTQ Satu Syawal di Desa Muara Potan - Muhammad Roihan Lubis; Muhammad Rizqi; Febri Wardani; Irpan Rambe (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Musabaqah Tilawatil Qur’an (MTQ) is a religious activity that plays an important role in improving Qur’anic recitation skills while fostering children's interest in learning the Qur’an. This study aimed to analyze the implementation of MTQ, identify its supporting and inhibiting factors, and examine its impact on improving the Qur’anic recitation abilities of children in Muara Potan Village, Kota Nopan District. The study employed a qualitative approach using a descriptive method. Data were collected through observations, interviews, and documentation and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the implementation of MTQ successfully enhanced children's interest, motivation, and Qur’anic recitation skills, as reflected by the increasing number of participants and the improvement in recitation quality over the years. The program's success was supported by strong collaboration among MDA teachers, community members, youth organizations, and parents. However, several challenges were identified, including limited funding, participant management, and reduced participation during the COVID-19 pandemic. Therefore, MTQ serves as an effective religious education program for strengthening children's Qur’anic reading competence and religious character in Muara Potan Village.